Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.17795/jjcdc-34852
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education Based on the Health Belief Model on Osteoporosis Prevention Behaviors in Female High School Students

Abstract: Background: Osteoporosis is one of the most common metabolic bone diseases and is the silent epidemic of this era. Objectives: This study evaluates the effect of education that is based on the health belief model on promoting osteoporosis prevention behaviors among female high school students. Methods: In this two-group interventional study, 172 students age 11 to 14 years (experimental group = 86 subjects; control group = 86 subjects) were randomly selected from Khorramshahr high schools using multistage samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In a systematic study conducted in Iran, the reported prevalence of low bone density among women was 51%, and the prevalence of osteoporosis was 32% [ 4 ]. According to the Tehran Rheumatology Research Center, over 6 million have osteoporosis [ 5 - 7 ]. Furthermore, approximately 1 woman in 3 women and 1 man in 12 men have osteoporosis in Iran [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic study conducted in Iran, the reported prevalence of low bone density among women was 51%, and the prevalence of osteoporosis was 32% [ 4 ]. According to the Tehran Rheumatology Research Center, over 6 million have osteoporosis [ 5 - 7 ]. Furthermore, approximately 1 woman in 3 women and 1 man in 12 men have osteoporosis in Iran [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, there were significant between-group differences in the mean score of physical activity four and two months after the intervention, respectively. 22,23 The final meta-analysis (156 participants in the intervention and 156 in the control groups) showed the ineffectiveness of education on this outcome (MD = 2.66, 95% CI = -0.55 to 5.88, P = 0.10) (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, different adolescent education models and theories have been used as an intervention. HBM (Health Belief Model) is one of the most useful models used in some studies 2025,29 and Planned Behavior Theory has been used in two studies. 33,34 Brown and Schoenly used OPTION program (Osteoporosis Prevention Teaching in Our Nation’s Schools) for education in the intervention group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations